Future Spacecraft Propulsion Systems and Integration Enabling Technologies for Space Exploration - Czysz, Paul A.; Bruno, Claudio; Chudoba, Bernd; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2018)
The updated and expanded third edition of this book focuses on the multi-disciplinary coupling between flight-vehicle hardware alternatives and enabling propulsion systems. It discusses how to match near-term and far-term aerospace vehicles to missions and provides a comprehensive overview of the subject, directly contributing to the next-generation space infrastructure, from space tourism to space exploration. This holistic treatment defines a mission portfolio addressing near-term to long-term space transportation needs covering sub-orbital, orbital and escape flight profiles. In this context, a vehicle configuration classification is introduced covering alternatives starting from the dawn of space access. A best-practice parametric sizing approach is introduced to correctly design the flight vehicle for the mission. This technique balances required mission with the available vehicle solution space and is an essential capability sought after by technology forecasters and strategicplanners alike.
Overview -- Our progress appears to be impeded -- Commercial near-Earth space launcher: a perspective -- Commercial near-Earth launcher: propulsion -- Earth orbit on-orbit operations in near-Earth orbit, a necessary second step -- Earth-Moon system: establishing a Solar System presence -- Exploration of our Solar System -- Stellar and interstellar precursor missions -- View to the future and exploration of our Galaxy.
Keywords: Aerospace engineering; Astronautics; Solar system; Aerospace Technology and Astronautics; Space Physics